Ectopic Bone Formation after Medial Femoral Condyle Graft to Scaphoid Nonunion - Vedung, Torbjörn; Vinnars, Bertil (Journal of Wrist Surgery, 2014)
Free vascularized bone graft from the medial femoral condyle has been described as a superior method for treatment of recalcitrant scaphoid nonunion with proximal pole avascularity and humpback deformity. Few complications and high union rates have been reported. In a series of three patients we describe an undesired volar ossification as a potential complication of the method. The risk of developing the ectopic bone formation can be minimized if the surgeon is aware of the strong osteogenic capacity of the periosteum. Meticulous dissection of the vascular bundle to the graft is mandatory to avoid the complication. Caution is warranted so as not to leave a periosteal sleeve under the vessels at the margin of the graft.
Keywords: ectopic bone formation; free vascularized bone graft; medial femoral condyle; ossification; scaphoid nonunion